HUR protects NONO from degradation by mir320, which is induced by p53 upon UV irradiation - Alfano, Luigi (Oncotarget, 2016)
UV radiations challenge genomic stability and are a recognized cancer risk factor. We previously found that the RNA-binding protein NONO regulates the intra-S phase checkpoint and its silencing impaired HeLa and melanoma cell response to UV-induced DNA damage. Here we investigated the mechanisms underlying NONO regulation upon UVC treatment. We found that UVC rays induce the expression of mir320a, which can indeed target NONO. However, despite mir320a induction, NONO mRNA and protein expression are not affected by UVC. We found through RNA immunoprecipitation that UVC rays induce the ubiquitous RNA-binding protein HUR to bind NONO 5′UTR in a site overlapping mir320a binding site. Both HUR silencing and its pharmacological inhibition induced NONO downregulation following UVC exposure, whereas concomitant mir320a silencing restored NONO stability. UVC-mediated mir320a upregulation is triggered by p53 binding to its promoter, which lies within a region marked by H3K4me3 and H3K27ac signals upon UVC treatment. Silencing mir320a sensitizes cells to DNA damage. Overall our findings reveal a new mechanism whereby HUR protects NONO from mir320-mediated degradation upon UVC exposure and identify a new component within the complex network of players underlying the DNA damage response adding mir320a to the list of p53-regulated targets upon genotoxic stress.